bạn cho các đa thức A(x) , B(x),C(x) =0 rồi giải nha !
\(A(x)=(2x-4)(x+1)=0\)
\(\Leftrightarrow\orbr{\begin{cases}2x-4=0\\x+1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
Vậy đa thức \(A(x)\)có hai nghiệm đó là 2 và -1
\(B(x)=(-5x+2)(x-7)=0\)
\(\Leftrightarrow\orbr{\begin{cases}-5x+2=0\\x-7=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}-5x=-2\\x=7\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{2}{5}\\x=7\end{cases}}\)
Vậy đa thức \(B(x)\)có hai nghiệm đó là 2/5 và 7
\(C(x)=(4x-3)(2x+3)=0\)
\(\Leftrightarrow\orbr{\begin{cases}4x-3=0\\2x+3=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{3}{4}\\x=-\frac{3}{2}\end{cases}}\)
Vậy đa thức \(C(x)\)có hai nghiệm đó là 3/4 và -3/2
1) (2x - 4)(x + 1) = 0
2x - 4 = 0 hoặc x + 1 = 0
2x = 0 + 4 x = 0 - 1
2x = 4 x = -1
x = 4/2
x = 2
=> x = 2 hoặc x = -1
2) (-5x + 2)(x - 7) = 0
-5x + 2 = 0 hoặc x - 7 = 0
-5x = 0 - 2 x = 0 + 7
-5x = -2 x = 7
x = 2/5 x = 7
=> x = 2/5 hoặc x = 7
3) (4x - 3)(2x + 3) = 0
4x - 3 = 0 hoặc 2x + 3 = 0
4x = 0 + 3 2x = 0 - 3
4x = 3 2x = -3
x = 3/4 x = -3/2
=> x = 3/4 hoặc x = -3/2